Late gadolinium enhancement assessed by cardiac magnetic resonance imaging in heart transplant recipients with different stages of cardiac allograft vasculopathy - Braggion-Santos, Maria F.; Loßnitzer, Dirk; Buß, Sebastian Johannes; Lehrke, Stephanie; Dösch, Andreas; Giannitsis, Evangelos; Korosoglou, Grigorios; Katus, Hugo; Steen, Henning (European heart journal - cardiovascular imaging, 2014)
AbstractAims. Cardiac allograft vasculopathy (CAV), which limits long-term survival after heart transplantation (HTX), is usually evaluated by coronary angiogr
Gesehen am 15.07.2020